2014
DOI: 10.7181/acfs.2014.15.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermal Matrix to Treat Full Thickness Skin Defects: Follow-Up Subjective and Objective Skin Quality Assessments

Abstract: BackgroundThere are several options for replacement of the dermal layer in full-thickness skin defects. In this study, we present the surgical outcomes of reconstruction using acellular dermal substitutes by means of objective and subjective scar assessment tools.MethodsWe retrospectively reviewed the medical records of 78 patients who had undergone autologous split-thickness skin graft with or without concomitant acellular dermal matrix (CGDerm or AlloDerm) graft. We examined graft survival rate and evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…Despite the many documented advantages of autologous split-thickness grafting scar contracture, loss of elasticity and unfavorable aesthetic results remain a considerable problem. 1 The transition between the graft and normal skin is typically very sharp and can frequently be hypertrophic. We describe a novel use of pinking shears to create a serrated edge on both the skin graft and the recipient defect, thereby rendering the transition point between the two less obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many documented advantages of autologous split-thickness grafting scar contracture, loss of elasticity and unfavorable aesthetic results remain a considerable problem. 1 The transition between the graft and normal skin is typically very sharp and can frequently be hypertrophic. We describe a novel use of pinking shears to create a serrated edge on both the skin graft and the recipient defect, thereby rendering the transition point between the two less obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Dermal grafts obtained from human subjects have been used to treat burns and full-thickness skin defects [80, 81]. However, their applicability is limited by their high cost, the limited availability of cadaver skin, and the risk of disease transmission [82].…”
Section: Scaffolds From Extracellular Matrixmentioning
confidence: 99%
“…The ADM is the remaining ECM of the dermal and basement membranes once the cellular components (the epidermis and the cells of the dermis) have been removed and can provide the mechanical support lacking at the wound site, improve the quality of wound healing, increase the survival rate of the epidermal membrane, and prevent wound contraction and scar formation [ 79 ]. Dermal grafts obtained from human subjects have been used to treat burns and full-thickness skin defects [ 80 , 81 ]. However, their applicability is limited by their high cost, the limited availability of cadaver skin, and the risk of disease transmission [ 82 ].…”
Section: Scaffolds From Extracellular Matrixmentioning
confidence: 99%
“…[ 4 ] With this approach, through a short dorsal incision at the base of the penis, the scar is concealed in a crease covered by pubic hair and thus hardly visible. Although a survey conducted by Tealab et al showed that penile augmentation by porcine acellular dermal grafts might negatively affect male sexual status (4 in 18 patients reported decreased penile sensation at 6-month visit), [ 5 ] penile enlargement by implantation of ADM was a safe and effective operation in most of the reports [ 4 , 6 ] and, no major complications occurred in the patients received penile augmentation by ADM. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%